Particulate organic matter release below melting sea ice (Terra Nova Bay, Ross Sea, Antarctica): Possible relationships with zooplankton - Cau A.; Ennas C.; Moccia D.; Mangoni O.; Bolinesi F.; Saggiomo M.; Granata A.; Guglielmo L.; Swadling K. M.; Pusceddu A. (Journal of Marine Systems, 2021)
Timing and rates of release of particulate organic matter (POM) beneath the Antarctic sea ice during the melting season are relatively unknown. To shed light on this topic, we investigated: i) quantity and biochemical composition of POM released below annual sea ice in Terra Nova Bay (TNB, Ross Sea, Antarctica) through sediment traps deployed at 10- and 30-m depth; ii) the abundance and taxonomic composition of phytoplankton; iii) the abundance and biochemical composition of two zooplankton species, namely the pteropods Clione limacina antarctica and Limacina helicina antarctica. Overall, our results show that in late spring-early summer in TNB the melting of annual sea ice determines a rapid release of particles into the underlying water column, and that those particles are transported downward at the rate of hours to days. POM fluxes were dominated by lipids, which probably resulted from zooplankton grazing activity on sea-ice algae and faecal pellets that were released into the water column. This, after the initial injection of particles, which were likely associated with sinking sympagic microalgal biomass derived from the sea ice melting, enhanced the nutritional value of POM. POM released beneath the sea ice, in turn, had a possible effect on the biochemical composition of the two pteropod species. Our results confirm that melting of sea ice in spring-summer each year in Antarctic coastal waters represents a fundamental step in the transfer of energy towards the higher trophic levels. Evidence of a decline in Antarctic sea ice over the last five years, plausibly as a consequence of global warming, underlines a conspicuous decline in habitat availability for sea-ice algae and, as a consequence, a drop in the availability of food for pteropods and the higher trophic levels of the coastal Antarctic Ocean.